2023
DOI: 10.1021/acs.analchem.2c05704
|View full text |Cite
|
Sign up to set email alerts
|

Regions of Interest Multivariate Curve Resolution Liquid Chromatography with Data-Independent Acquisition Tandem Mass Spectrometry

Abstract: New data-independent acquisition (DIA) modes coupled to chromatographic separations are opening new perspectives in the processing of massive mass spectrometric (MS) data using chemometric methods. In this work, the application of the regions of interest multivariate curve resolution (ROIMCR) method is shown for the simultaneous analysis of MS1 and MS2 DIA raw data obtained by liquid chromatography coupled to quadrupole-timeof-flight MS analysis. The ROIMCR method proposed in this work relies on the intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Thus, the proposed ROIMCR allows the direct linking and correspondence between the MS signals in the four acquisition modes (MS1( +)/MS2( +)/MS1(-)/MS2(-)), for the same chemical species (see Tables 2 and S5 ), when performing their simultaneous analysis. Linking the spectra of the different amino acids in their four acquisition modes facilitates their coverage, identification, and possible quantitation [ 20 ]. Table S5 (in Supplementary Information) describes the list of MS2 fragment ions obtained in the ROIMCR analysis, confirmed by the literature database, that facilitated the annotation and identification of the amino acids in the standard sample.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the proposed ROIMCR allows the direct linking and correspondence between the MS signals in the four acquisition modes (MS1( +)/MS2( +)/MS1(-)/MS2(-)), for the same chemical species (see Tables 2 and S5 ), when performing their simultaneous analysis. Linking the spectra of the different amino acids in their four acquisition modes facilitates their coverage, identification, and possible quantitation [ 20 ]. Table S5 (in Supplementary Information) describes the list of MS2 fragment ions obtained in the ROIMCR analysis, confirmed by the literature database, that facilitated the annotation and identification of the amino acids in the standard sample.…”
Section: Resultsmentioning
confidence: 99%
“…MCR can be performed separately for each chromatographic run using one acquisition and ionization mode or simultaneously using multiple chromatographic runs and acquisition, as described by Pérez-López et al [ 20 ], and ionization positive and negative modes, as shown in the following Eqs. 2 , 3 , 4 , and 5 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations